2010
DOI: 10.1063/1.3511334
|View full text |Cite
|
Sign up to set email alerts
|

Sequential tunneling transport characteristics of GaN/AlGaN coupled-quantum-well structures

Abstract: Vertical electronic transport in periodic GaN/AlGaN multiple-quantum-well structures grown on free-standing GaN substrates is investigated. Highly nonlinear current-voltage characteristics are measured, displaying a clear transition from a high-resistance state near zero applied bias to a low-resistance state as the voltage is increased. The measurement results, including their temperature dependence and the variations in turn-on voltage with subband structure and bias polarity are in full agreement with a pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Sequential tunneling devices rely on repeated tunneling and scattering of carriers through up to several hundred periods of a structure. It was first demonstrated in nitride devices by Sudradjat et al 36 with 20-30 three-well periods of an Al 0.15 Ga 0.85 N/GaN structure at low temperature with good agreement between the experimental and predicted subbandalignment voltages. Following this, a thinner structure with 10 periods of a single well and AlN barriers was grown and compared with analytical expressions 25 for current; however, it was found that domain formation dominates the I-V characteristics, preventing investigation into the roles of scattering on transport.…”
Section: Introductionmentioning
confidence: 80%
“…Sequential tunneling devices rely on repeated tunneling and scattering of carriers through up to several hundred periods of a structure. It was first demonstrated in nitride devices by Sudradjat et al 36 with 20-30 three-well periods of an Al 0.15 Ga 0.85 N/GaN structure at low temperature with good agreement between the experimental and predicted subbandalignment voltages. Following this, a thinner structure with 10 periods of a single well and AlN barriers was grown and compared with analytical expressions 25 for current; however, it was found that domain formation dominates the I-V characteristics, preventing investigation into the roles of scattering on transport.…”
Section: Introductionmentioning
confidence: 80%
“…However, the lattice-mismatch at interfaces cause many effects such as spontaneous and piezoelectric polarization, polarization induced interface roughness, high dislocation density, and other structural defects. In general, the above effects are the main roadblock for the limitation of the efficiency of the optoelectronic devices [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…8, the population inversion and hence the gain coefficient of the GaN/AlGaN QWs dependence on the temperature is three times smaller than that of GaAs/ AlGaAs for THz emission and the gain coefficient of the nitride device remain large enough for laser action even without cryogenic cooling. [109][110][111] As a result, GaN-based devices can operate in the upper THz frequency of 5 to 10 THz at room temperature, which is inaccessible by GaAs-based devices. 86 In 2003, pioneer works reported THz emission from InGaN/GaN multiple QWs.…”
Section: Gan-based Quantum Cascade Lasersmentioning
confidence: 99%